Neuroimmune Regulation in Sepsis-Associated Encephalopathy: The Interaction Between the Brain and Peripheral Immunity - Liu, Yu-xiao; Yu, Yang; Liu, Jing-peng; Liu, Wen-jia; Cao, Yang; Yan, Run-min; Yao, Yong-ming (Frontiers in Neurology, 2022)
Sepsis-associated encephalopathy (SAE), the most popular causation of coma in the intensive care unit (ICU), is the diffuse cerebral damage caused by the septic challenge. SAE is closely related to high mortality and extended cognitive impairment in septic patients. At present, many studies have demonstrated that SAE might be mainly associated with blood-brain barrier damage, abnormal neurotransmitter secretion, oxidative stress, and neuro-immune dysfunction. Nevertheless, the precise mechanism which initiates SAE and contributes to the long-term cognitive impairment remains largely unknown. Recently, increasing evidence has been indicated that there is close crosstalk between SAE and peripheral immunity. The excessive migration of peripheral immune cells to the brain, the glia activation, and the resulting central immune dysfunction are the main causes of septic nerve damage. This paper reviews the update on the pathogenesis of septic encephalopathy, focusing on the over-activation of immune cells in the central nervous system(CNS) and the "neurocentral-endocrine-immune" networks in the development of SAE, aiming to further understand the potential mechanism of SAE and provide the new targets for diagnosis and management of septic complications.